Productive use of learning resources in an online problem-based learning environment. - Jeong, Heisawn; Hmelo-Silver, Cindy E. (Computers in Human Behavior, 2010)
This study examined students' use of learning resources in a technologically-mediated online learning environment. Undergraduate student groups were engaged in an online problem-based learning (PBL) environment, rich with pre-selected video and knowledge resources. Quantitative and qualitative analyses showed that students accessed resources fairly frequently and benefited from them. Resources helped students construct a rich understanding of the problem and provided ideas for problem solutions. Detailed analyses of resource exploration along with contrasting case analyses between high-achieving and low-achieving student groups suggested that for learning to be effective in resource-rich environments, students first need to develop an understanding of the resources and learn how to access them efficiently. Second, students need to learn to process the contents of resources in meaningful ways so that they can integrate diverse resources to form a coherent understanding and apply them to solve problems. Finally, students need to develop knowledge and skills to use resources collaboratively, such as sharing and relating to each other's resources. The results indicated that students, especially low-achieving students, need guidance to use resources effectively in resource-rich learning environments. Copyright (c) 2009 Elsevier Ltd.